Correction: Recent advances in the methanol synthesis via methane reforming processes. Issue 56 (14th September 2020) - Rashid, Muhammad Usman; Wan Daud, W. M. A.
Abstract : Correction for 'Recent advances in the methanol synthesis via methane reforming processes' by Muhammad Usman Rashid et al., RSC Adv., 2015, 5, 21945–21972, DOI: ; 10.1039/C4RA15625K .